EFEKTIVITAS MEDIA LEMBAR BALIK DAN LEAFLET TERHADAP PENINGKATAN PENGETAHUAN DAN SIKAP MASYARAKAT TENTANG PENGELOLAAN SAMPAH RUMAH TANGGA DI DESA GRAJAGAN KABUPATEN BANYUWANGI - Puji Lestari; Septia Dwi Cahyani; Irfany Rupiwardani (Jurnal Multidisipliner Kapalamada, 2026)
Household waste remains a serious environmental issue, particularly in rural areas with low levels of waste management. Community education through health promotion media is needed to improve knowledge and attitudes toward household waste management. This study aimed to analyze the effectiveness of flipchart and leaflet media in improving community knowledge and attitudes regarding household waste management in Grajagan Village, Banyuwangi Regency. A quasi-experimental study with a pretest–posttest control group design was conducted. A total of 384 housewives were selected as respondents and divided into two groups, receiving education using flipchart and leaflet media, respectively. Data were analyzed using Paired Samples T-Test and Independent Samples T-Test. The results showed that both media significantly increased respondents’ knowledge and attitudes (p < 0.05); however, leaflet media was more effective than flipchart media, as indicated by higher gains in knowledge and attitude scores. Leaflet media is therefore recommended as an effective and practical educational tool for environmental health promotion.